Perkawinan Dini Dan Tantangan Tanggung Jawab Keuangan Di Sibuhuan Kabupaten Padang Lawas - Pane, Erwin (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
This research will examine the responsibilities of husbands when carrying out early marriages in Sibuhuan, Padang Lawas Regency, using field research and a qualitative approach. The primary source is in the form of direct interviews with perpetrators of early marriage. Next, it is analyzed using descriptive analysis techniques. This research shows that husbands who enter into early marriages have not been able to fulfill their responsibilities as husbands because. First, minor children have few job opportunities; they have weak energy and unstable emotions; third, they have inadequate knowledge and no expertise; and fourth, internal conflicts often occur in the family, both between husband and wife and parents.